‘The Good Girl from Russia Can Do it All’: 'Au pairs’ perspective on morality and immorality in the au pair relation' - Caterina Rohde-Abuba (Nordic Journal of Migration Research, 2016)
This article investigates the perspectives of au pairs on conflicts and exploitation during the au pair stay. Theoretically based on the concept of moral economy, it will be shown that au pairs disidentify with professional domestic and care workers to maintain their identity of an international student acting as a helper for a local family struggling with childcare. Referring to moral norms, au pairs react to conflicts by using the strategy of ‘shaming’ to protest against dissatisfying conditions of au pairing, or they decide to change to another family. These forms of resistance are legitimised in narratives, which in processes of othering establish a moral hierarchy between the au pair and family to reject victimisation of exploitation and demonstrate their own capability to act as an independent adult person.